2018
DOI: 10.1093/imrn/rny110
|View full text |Cite
|
Sign up to set email alerts
|

The Limit Point of the Pentagram Map

Abstract: The pentagram map is a discrete dynamical system defined on the space of polygons in the plane. In the first paper on the subject, R. Schwartz proved that the pentagram map produces from each convex polygon a sequence of successively smaller polygons that converges exponentially to a point. We investigate the limit point itself, giving an explicit description of its Cartesian coordinates as roots of certain degree three polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…In 1992 I wrote a paper [13] defining the pentagram map for general n-gons and proving in the convex case that the forward orbit shrinks to a point. Very recently, M. Glick [2] found a kind of formula for this collapse point.…”
Section: Contextmentioning
confidence: 95%
See 1 more Smart Citation
“…In 1992 I wrote a paper [13] defining the pentagram map for general n-gons and proving in the convex case that the forward orbit shrinks to a point. Very recently, M. Glick [2] found a kind of formula for this collapse point.…”
Section: Contextmentioning
confidence: 95%
“…Each of these two level sets is the disjoint union of a diagonal line and a circle. The map T 2 3 preserves each component and acts there with order 3. For example…”
Section: Special Casesmentioning
confidence: 99%
“…The pentagram map, T 2 , is one of the best known discrete completely integrable system. See for instance, [1], [2], [3], [8], [9], [10], [11], [12], [14], [15], [21], [22]. The Pentagram Rigidity Conjecture would be a statement about the global topology of an abelian foliation associated to a completely integrable system if the map T 3 were known to be completely integrable.…”
Section: Contextmentioning
confidence: 99%
“…The deeper diagonal maps D k , k > 2, are also completely integrable. Incidentally, the Poncelet grid theorem implies that the pentagram map sends a Poncelet polygon to a projectively equivalent one.2) As a by-product of the study of the pentagram map, eight new projective configuration theorems were found in [17]; see also [20].3) To quote from Kasner [9], Among the corollaries ... the most interesting is this (valid for at least convex pentagons): The limit point of the sequence of successive inscribed pentagons coincides with the limit point of the sequence of successive diagonal pentagons.In this respect, see [7] for a recent striking result on the limiting point of the pentagram map acting on convex n-gons (before factorization by the projective group). 4) Poncelet theorem and its ramifications continue to be an active research area.…”
mentioning
confidence: 99%
“…In this respect, see [7] for a recent striking result on the limiting point of the pentagram map acting on convex n-gons (before factorization by the projective group). 4) Poncelet theorem and its ramifications continue to be an active research area.…”
mentioning
confidence: 99%